International Communism in the era of Lenin : a documentary history - Gruber, Helmut (Greenwich : Fawcett Publications, 1967)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Derde Internationale (1919-1943).; Lenin, Vladimir Iljitsj; Oktoberrevolutie; marxisme-leninisme